CONCEPT OF EUROPEAN VALUES STUDY IN THE INTER-DISCRIMINAL MEASUREMENT: REFLEXION AND PRACTICE - Комісар, Л. П.; Чехун, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The research covers a range of issues related to the timely reception of the concept of "European values" in modern practical philosophy, revealing the interdisciplinary components of the concept "European Values Study". In this context, European values are one of the leading communicative models of a modern globalized society in the universalist sense.